Comorbidity And Life Quality Of The Elderly - Гакман; Hakman, Анна; Anna; DUDITSKA, SVITLANA; Medvid, Angela; Tymchuk, Liudmyla; Koshura, Andrii; Huliaieva, Mariia; Yachniuk, Maksym; Mykyteichuk, Khrystyna (7th International Conference of the Universitaria Consortium In Physical Education, Sports and Physiotherapy, Iasi, Romania, 2021)
The article addresses the issue of increasing the effectiveness of the use of health-promoting and recreational physical activities to improve life quality and satisfaction in the elderly. The relevance of the study is due to the fact that the progressive aging of the population in most countries of the world, including in Ukraine, is accompanied by a corresponding increase in the number of people with multiple health conditions that affect their quality of life. The purpose of the study was to determine the morbidity structure and quality of life of the elderly and to explore the possibilities of the use of health-promoting and recreational activities at the universities of the third age to improve the physical and psycho-emotional status of this group of population. To achieve the goal, the following methods were used: theoretical analysis of the data from specialized scientific and methodological literature, documentary materials, comparative analysis, data extraction from medical records, methods of assessing the morbidity structure (Cumulative Illness Rating Scale), level of satisfaction (The Satisfaction with Life Scale (SWLS)), and quality of life (36-Item Short Form Health Survey (SF-36) with modifications), methods of mathematical statistics. The study involved 91 individuals aged 60-75 years (with a mean age of 67.3 years). The study was conducted at the universities of the third age (Chernivtsi). Research results. Priority groups of diseases of the elderly, which include diseases of the organs of the musculoskeletal system (muscles, joints, and bones) and skin, diseases of the cardiovascular system, diseases of the sense organs, diseases of the nervous system, etc., were identified. It is revealed that a considerable part of the elderly have a low level of life satisfaction and poor quality of life. Possibilities of involvement of the elderly in health-promoting and recreational physical activity at the base of the third-age universities were outlined. Conclusions. On the basis of theoretical and empirical research the morbidity and quality of life of the elderly were assessed. The study showed high prevalence of comorbidity in the older population that, in turn, affects the satisfaction and quality of life of the elderly.
Keywords: old age; morbidity; comorbidity; quality of life; satisfaction; health-promoting and recreational physical activity; third-age university